2013
DOI: 10.2528/pierb12120508
|View full text |Cite
|
Sign up to set email alerts
|

GPR Estimation of the Geometrical Features of Buried Metallic Targets in Testing Conditions

Abstract: Abstract-The capability of Ground Penetrating Radar (GPR) systems of accurately reconstructing the geometrical features of buried objects when working in critical conditions is investigated. A customized microwave tomographic approach is used to tackle the imaging through the processing of comparative experimental and synthetic GPR data. The first ones have been gathered in laboratory controlled conditions, while the second ones have been obtained by exploiting an ad-hoc implementation of a CAD tool. Attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…Direct knowledge of the velocity of the host medium also allows the usage of hyperbola fitting, with the radius of the rebar as the only unknown [37]. In [38] it is shown that using a Kirchoff-based linearized inversion can effectively recover some information regarding the shape of the targets regardless of the medium velocity. In the same context, a FWI approach is suggested in [39] to estimate the host medium properties and the size and depth of a steel rebar.…”
Section: Introductionmentioning
confidence: 99%
“…Direct knowledge of the velocity of the host medium also allows the usage of hyperbola fitting, with the radius of the rebar as the only unknown [37]. In [38] it is shown that using a Kirchoff-based linearized inversion can effectively recover some information regarding the shape of the targets regardless of the medium velocity. In the same context, a FWI approach is suggested in [39] to estimate the host medium properties and the size and depth of a steel rebar.…”
Section: Introductionmentioning
confidence: 99%
“…Let us observe that the characteristics of the input signal, in terms of waveform and relevant frequency spectrum, strongly influence the imaging capabilities, especially in critical conditions [ 7,8].…”
Section: Synthetic Setupmentioning
confidence: 99%
“…In this frame, an EM computer aided-design (CAD) simulation of the scenario under test is exploited [ 7]- [ 9]. This numerical setup allows us to accurately estimate the incident and the scattered fields to be considered in the inverse problem solution.…”
Section: Introductionmentioning
confidence: 99%
“…GPR data consist of target and clutter(direct wave, underground clutter and other noise signals) [3][4][5]. It is difficult to extract target signal especially in the shallow subsurface.…”
Section: Introductionmentioning
confidence: 99%